High-air-permeability pitch-based carbon fiber base paper and preparation process thereof

Through the combination of asphalt-based carbon fiber and aramid pulp and the low-concentration phenolic resin impregnation process, the problem of difficulty in taking into account the breathability, strength and flexibility of traditional carbon fiber paper is solved, and the improvement of high breathability and strength is achieved, providing a kind of High-performance carbon fiber raw paper and its preparation process.

CN119162862AActive Publication Date: 2024-12-20SHAANXI UNIV OF SCI & TECH

Patent Information

Application Number
CN202411374754.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-29
Publication Date
2024-12-20
Estimated Expiration
2044-09-29

AI Technical Summary

Technical Problem

Traditional carbon fiber paper is difficult to take into account high breathability, strength, conductivity and flexibility, and domestic manufacturing technology is relatively backward.

Method used

Asphalt-based carbon fiber is used as the skeleton, aramid pulp is used as auxiliary forming fibers, and low-concentration phenolic resin impregnation is used as reinforcement. High-breathability carbon fiber raw paper is prepared through ultrasonic cleaning, drying, relieving, forming, and hot pressing finishing.

Benefits of technology

It achieves the balance of high breathability, strength and flexibility of carbon fiber paper, solves the contradiction between conductivity and strength, and improves the comprehensive performance and market competitiveness of the paper.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119162862A_ABST
    Figure CN119162862A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of special papermaking and carbon fiber composite material preparation, in particular to high-air-permeability pitch-based carbon fiber base paper and a preparation technology thereof.The preparation method comprises the following steps that 1, pitch-based carbon fibers A are cleaned with diluted hydrochloric acid; dividing and brooming aramid fibers to obtain aramid pulp B; 2, performing wet forming on the pitch-based carbon fibers and the aramid pulp to obtain carbon fiber paper; and step 3, impregnating the pitch-based carbon fiber paper with phenolic resin, drying, and finishing to obtain the pitch-based carbon fiber base paper. The invention provides a novel method for preparing the high-air-permeability carbon fiber base paper through acid cleaning of carbon fibers, fibrillation of aramid fibers, wet forming of mixed pulp, resin impregnation strengthening and hot-pressing finishing, and the method comprises the steps that aramid pulp assists in interweaving, low-concentration resin strengthening is conducted, and the high-air-permeability carbon fiber base paper is obtained; the problem that strength, flexibility, high conductivity and high air permeability are difficult to consider at the same time is solved, and the high-air-permeability carbon fiber base paper and the preparation process thereof are provided.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the cross-technical field of special papermaking and carbon fiber-based material preparation, and specifically relates to a high-permeability asphalt-based carbon fiber base paper and a preparation process thereof. Background Art

[0002] Among the many new energy sources, fuel cells have high energy conversion efficiency, low pollution, low noise, and strong adaptability, and have received widespread attention. At present, fuel cells are mainly divided into alkaline fuel cells, proton exchange membrane fuel cells, solid oxide fuel cells, phosphoric acid fuel cells, etc. Among them, proton exchange membrane fuel cells use hydrogen, methanol and other fuels and are valued by the market. Proton exchange membrane fuel cells are mainly composed of bipolar plates, gas diffusion layers, proton exchange membranes, etc. The diffusion layer not only plays the role of supporting catalysts, but also serves as an important carrier for fuel gas diffusion, generated water extraction, heat extraction, and current collection. However, due to the existence of chemical corrosion, there are not many materials that can be used as fuel cell gas diffusion layers. Carbon paper is a material that has been successfully commercialized by international companies such as Japan's Toray and Germany's SGL, and has extremely high commercial potential and value.

[0003] Carbon paper is obtained by carbonizing, graphitizing and hydrophobizing carbon fiber paper. The structure and performance of carbon fiber paper determine the quality of the final carbon. However, the carbon fiber interface is highly inert and brittle, and it is difficult to prepare carbon fiber paper with high flexibility, high conductivity and high air permeability. In order to obtain carbon fiber paper with high air permeability, scientific and technological workers have successively glued carbon fibers with polyethanol, phenolic resin and the like, and then cured them at high temperature to obtain carbon fiber paper. A typical example is the patent US20180069245 of Mitsubishi Corporation of Japan, which glues carbon fibers with 15% polyvinyl alcohol to obtain flexible carbon fiber paper. Tse-Hao's patent US2006214320 obtains carbon paper with a deflection of 1.5 to 4.8 mm by mixing with cellulose and impregnating with phenolic resin; thereafter, Mikio et al.'s patent US6489051 prepares carbon paper by vinyl acetate, epoxy resin, melamine resin and the like, but there are problems of insufficient air permeability or newly introduced impurities. For a long time, due to the late start of carbon fiber in China, the carbon fiber paper manufacturing technology has been relatively backward. Summary of the invention

[0004] In view of the problem that the air permeability, strength, conductivity and flexibility of traditional carbon fiber base paper are difficult to be balanced, the present invention provides a high-permeability asphalt-based carbon fiber base paper and a preparation process thereof, which uses asphalt-based carbon fiber as a skeleton, aramid pulp as an auxiliary forming fiber, and low-concentration phenolic resin impregnation as a reinforcing agent to prepare the carbon fiber base paper, thereby solving the contradiction between the conductivity, strength, flexibility and air permeability of carbon fiber paper.

[0005] The present invention is achieved through the following technical solutions: A high-permeability asphalt-based carbon fiber base paper and a preparation process thereof, comprising the following steps: Step 1, soaking the asphalt-based carbon fiber in a dilute hydrochloric acid solution, and then ultrasonically cleaning and drying to obtain the asphalt-based carbon fiber A; The waste aramid fabric is subjected to filament separation and brooming by rolling, beating and refining to obtain aramid pulp B with high specific surface area, high terminal bifurcation and high interweaving force; Step 2: First, the aramid pulp B is deflated in water, and then the asphalt-based carbon fiber A and PEO dispersion are added to deflate again, and then the asphalt-based carbon fiber paper C is obtained by forming and drying; Step 3: The asphalt-based carbon fiber paper C is immersed in a phenolic resin dispersion solution, and then dried and hot-pressed to obtain an asphalt-based carbon fiber base paper with high air permeability.

[0006] Preferably, in step 1, the relevant requirements of the asphalt-based carbon fiber are as follows: length is 3-8 mm, diameter is 7-8 μm, resistivity is 1.5-2.0 μΩ·m, tensile strength is 2.2-2.4 Gpa, and elongation at break is 0.25%-0.26%; the concentration of dilute hydrochloric acid is 1-2%, the ultrasonic treatment time is 5-10 min, the drying temperature is 100-105°C, and the time is 15-25 min.

[0007] Preferably, in step 1, the waste aramid fabric is para-aramid fiber, which is mainly sourced from discarded bulletproof vests and scraps from woven fabric production.

[0008] Preferably, in step 1, the feeding time during thread rolling is 40-50 kg / h, the beating time during beating is 3-5 h, the refining time during refining is 0.5-1.0 h, and the specific surface area of ​​aramid pulp B is 10-12 m 2 / g.

[0009] Preferably, in step 2, the ratio of aramid pulp B to water is 1.0-1.2 g: 2 L, and the decomposition speed is 5000-6000 rpm.

[0010] Preferably, in step 2, the absolute dry mass ratio of the asphalt-based carbon fiber A to the aramid pulp B is 6-5:4, the concentration of the PEO dispersion is 0.5 g / L, the volume is 5-10 mL, and the disintegration speed is 20000-25000 rpm.

[0011] Preferably, in step 2, during drying, the temperature is 110-120° C. and the time is 10-15 min.

[0012] Preferably, in step 3, the phenolic resin dispersion solution is industrial grade ethanol, the mass fraction is 0.8 wt% to 1.0 wt%, and the immersion time is 5 to 10 min.

[0013] Preferably, in step 3, during drying, the temperature is 60-70° C. and the time is 20-30 min; during hot pressing finishing, the temperature is 150-180° C., the time is 5-8 min, and the pressure is 6-10 MPa.

[0014] A pitch-based carbon fiber base paper obtained by the process for preparing a high-permeability pitch-based carbon fiber base paper.

[0015] Compared with the prior art, the present invention has the following beneficial effects: First, the invention discloses a high-permeability asphalt-based carbon fiber base paper preparation process, which uses asphalt-based carbon fiber as a skeleton, aramid pulp as an auxiliary forming fiber, and low-concentration phenolic resin impregnation as a reinforcing agent to prepare a carbon fiber base paper with high permeability, thereby solving the contradiction between the conductivity, strength, flexibility, and permeability of carbon fiber paper. Compared with the disclosed process scheme, the raw material components are optimized and limited: on the one hand, aramid pulp fiber is introduced to improve the paper uniformity and promote fiber interlacing; on the other hand, low-concentration phenolic resin impregnation and bonding are used to avoid pore blocking. In this structure, the introduced aramid pulp molecular structure is composed of alternating benzene rings and amide bonds, and the molecular structure has a high carbon content, which is conducive to obtaining paper with higher conductivity after carbonization. At the same time, since the aramid pulp has good dispersibility after filamentization, the paper uniformity of the carbon fiber base paper can also be improved.

[0016] The introduced aramid pulp has good flexibility and adhesion. After being made into paper, it can not only improve the flexibility and strength of the paper, make up for the shortcomings of excessive brittleness and interface inertness of carbon fiber, but also form a rich conductive network after carbonization, which is conducive to improving the comprehensive conductive performance of paper and solving the contradiction between the strength, toughness and conductivity of carbon fiber. In addition, the proportion of aramid pulp is obtained through long-term process optimization. If the content of aramid pulp is too high, it is not conducive to resin impregnation and is easy to block the pore structure of paper. If the content of aramid pulp is too low, the uniformity of paper is not significantly improved and the flexibility is insufficient.

[0017] Furthermore, the present invention, based on the introduction of aramid pulp as an auxiliary, realizes the adhesion and reinforcement of the interweaving points between carbon fibers and carbon fibers, between carbon fibers and aramid pulp, and between aramid pulp through the impregnation of ultra-low concentration phenolic resin; the concentration of phenolic resin is the result of process optimization. At ultra-low concentration, it not only ensures the supplement of insufficient fiber contact points, facilitates the construction of a conductive network after subsequent carbonization, but also realizes full strength and the transmission of stress during the stretching process, ensuring the realization of paper performance.

[0018] Furthermore, the preferred aramid pulp terminal groups in the present invention contain rich amino groups, have good compatibility and self-binding ability with phenolic resin, and ensure high performance at low concentration. The principle is that the aramid pulp terminal groups can form extensive hydrogen bonds with the resin, and the curing of the phenolic resin can cross-link the aramid pulp fiber filaments. Therefore, the two can achieve high-strength bonding through the combined action of chemistry and physics, which is not found in other public invention patents. The realization of this principle is one of the unique technical points of the present invention.

[0019] Furthermore, the pulp decomposition speed, fiber adding sequence, drying temperature, hot pressing finishing temperature and hot pressing finishing pressure in the present invention are all the results of process optimization. For example, the pulp decomposition speed ensures no breakage under high dispersion, the drying temperature ensures energy saving under high efficiency, and the finishing temperature ensures no rheological blockage under phenolic resin curing. These are all the results of long-term process optimization, and the technical effect is to improve paper quality and save energy. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 This is a flow chart of a process for preparing a high-permeability asphalt-based carbon fiber base paper according to the present invention; Figure 2 This is the cross-sectional SEM image of the carbon fiber paper of Example 3.

[0021] It can be seen more clearly in the figure that the carbon fiber and aramid pulp form an interwoven network with a gas channel in the middle, which explains the reason for the high air permeability.

[0022] Figure 3 This is the SEM image of the surface of the carbon fiber paper in Example 4.

[0023] As can be seen in the figure, carbon fiber and aramid pulp are interwoven and have abundant pores. DETAILED DESCRIPTION

[0024] The present invention is further described in detail below in conjunction with specific embodiments, which are intended to explain the present invention rather than to limit it.

[0025] The present invention discloses a high-permeability asphalt-based carbon fiber base paper and a preparation process thereof, comprising the following steps: Step 1, soaking the asphalt-based carbon fiber in a dilute hydrochloric acid solution, and then ultrasonically cleaning and drying to obtain asphalt-based carbon fiber A; specifically: selecting an asphalt-based carbon fiber with a length of 3 to 8 mm, a diameter of 7 to 8 μm, a resistivity of 1.5 to 2.0 μΩ·m, a tensile strength of 2.2 to 2.4 Gpa, and an elongation at break of 0.25% to 0.26%, soaking it in a dilute hydrochloric acid solution with a concentration of 1 to 2%, and ultrasonically cleaning it for 5 to 10 minutes, and drying it at a temperature of 100 to 105°C for 15 to 25 minutes to obtain asphalt-based carbon fiber A; Waste aramid fabrics composed of retired bulletproof vests and scraps from woven fabric production are subjected to filament separation and grinding by thread rolling, beating and grinding to obtain aramid pulp B with high specific surface area, high terminal bifurcation and high interweaving force; The thread rolling is carried out by a thread rolling machine, the model of the thread rolling machine is TMF250, and the feeding time of the thread rolling machine is 40-50 kg / h; the pulping is carried out by a pulping machine, the model of the pulping machine is a trough type pulping machine 220, and the pulping time is 3-5 hours; the model of the pulping machine is 380, and the pulping time is 0.5-1.0 hours; the specific surface area of ​​aramid pulp B is 10-12 m 2 / g.

[0026] Step 2: Now, aramid pulp B and water are deflaked at a ratio of (1.0-1.2) g: 2 L, and the speed during deflaking is (4500-5000) rpm; Then, the asphalt-based carbon fiber A is added according to the absolute dry mass ratio of the asphalt-based carbon fiber A to the aramid pulp B (6-5):4, and then 5-10 mL of a PEO dispersion having a concentration of 0.5 g / L is added, and then the mixture is dispersed uniformly at 20000-25000 rpm to obtain a mixed slurry; The mixed slurry is passed through a paper sheet former to make paper, and after the paper is formed, it is dried at 110 to 120° C. for 10 to 15 minutes to obtain asphalt-based carbon fiber paper C.

[0027] Step 3: Immerse the asphalt-based carbon fiber paper C in a phenolic resin dispersion (industrial grade ethanol) with a mass fraction of 0.8 wt% to 1.0 wt% for 5 to 10 minutes; Then, the asphalt-based carbon fiber paper C is dried at 60-70° C. for 20-30 min to obtain a dry asphalt-based carbon fiber paper D; Then, the dry asphalt-based carbon fiber paper D is hot-pressed and finished using a flat vulcanizer at a temperature of 150 to 180° C., a time of 5 to 8 minutes, and a pressure of 6 to 10 MPa to obtain an asphalt-based carbon fiber base paper with high air permeability.

[0028] In a high-permeability asphalt-based carbon fiber base paper preparation process of the present invention, the asphalt-based carbon fiber A is first cleaned with dilute hydrochloric acid; the aramid fiber is split and broomed to obtain aramid pulp B; the asphalt-based carbon fiber and aramid pulp are wet-formed to obtain carbon fiber paper; finally, the asphalt-based carbon fiber paper is impregnated with phenolic resin, dried, and finished to obtain the asphalt-based carbon fiber base paper. A new method for preparing carbon fiber base paper with high permeability by acid cleaning carbon fiber, splitting and brooming aramid fiber, wet forming of mixed slurry, resin impregnation reinforcement and hot pressing finishing, the method solves the problem of strength, flexibility, high conductivity and high permeability being difficult to take into account through aramid pulp auxiliary interweaving and low-concentration resin reinforcement, and provides a high-permeability carbon fiber base paper and a preparation process thereof.

[0029] The process scheme of the present invention uses conventional equipment such as a deflaker, a paper sheet former, a dryer, and a hot press, and the solvents are tap water and ethanol. The process steps are environmentally friendly, which lays a good foundation for the industrialization and scale-up of the technology of the present invention and has a high market competitive advantage.

[0030] The invention also discloses an asphalt-based carbon fiber base paper obtained by a high-permeability asphalt-based carbon fiber base paper preparation process.

[0031] Example 1 Step 1, selecting a pitch-based carbon fiber with a length of 3 mm, a diameter of 7 μm, a resistivity of 1.5 μΩ·m, a tensile strength of 2.2 Gpa, and an elongation at break of 0.25%, soaking it in a 2% dilute hydrochloric acid solution, ultrasonically cleaning it for 10 minutes, and drying it to obtain a pitch-based carbon fiber A; The waste aramid fabric was separated and refined by a thread rolling machine, a pulping machine, a pulping machine and other equipment to obtain a specific surface area of ​​10 m 2 / g aramid pulp B; Among them, the feeding time of the thread rolling machine is 40kg / h, the beating time is 3h, and the grinding time is 0.5h.

[0032] Step 2: disintegrate the aramid pulp B in water at 6000 rpm according to the volume ratio of aramid pulp B to water of 1.0 g: 2 L; Asphalt-based carbon fiber A was added according to the absolute dry mass ratio of asphalt-based carbon fiber A to aramid pulp B of 6:4, and then 5 mL of PEO solution with a concentration of 0.5 g / L was added, and then the mixture was dispersed uniformly at 20,000 rpm to obtain a mixed slurry; The mixed slurry was passed through a paper former to make paper, and after the paper was formed, it was dried at 110° C. for 10 min to obtain asphalt-based carbon fiber paper C.

[0033] Step 3: Immerse the asphalt-based carbon fiber paper C in a phenolic resin dispersion having a mass fraction of 0.8 wt% for 5 minutes, and then dry it at a temperature of 60° C. for 20 minutes to obtain a dry asphalt-based carbon fiber paper D; The dried asphalt-based carbon fiber paper D was hot-pressed and finished using a flat vulcanizer at 150° C., for 5 min, and at a pressure of 6 MPa to obtain an asphalt-based carbon fiber base paper with high air permeability.

[0034] The carbon fiber base paper prepared by the high permeability asphalt-based carbon fiber base paper preparation process in this embodiment has a basis weight of 85g / m 2The thickness is 0.153mm, the air permeability reaches 8104 mL / min, the tensile strength is 21.29 MPa, and the square resistance is 18.06Ω / sq, which has high air permeability. In addition, the process flow is stable, the operability is strong, the comprehensive cost is controllable, and it has good social and economic benefits.

[0035] Example 2 Step 1, selecting a pitch-based carbon fiber with a length of 8 mm, a diameter of 8 μm, a resistivity of 2.0 μΩ·m, a tensile strength of 2.4 Gpa, and an elongation at break of 0.26%, soaking it in a 1.5% dilute hydrochloric acid solution, ultrasonically cleaning it for 8 minutes, and drying it to obtain a pitch-based carbon fiber A; The waste aramid fabric was separated and refined by a thread rolling machine, a pulping machine, a pulping machine and other equipment to obtain a specific surface area of ​​12 m 2 / g of aramid pulp B; wherein, the feeding time of the thread rolling machine is 50kg / h, the beating time is 3-5h, the refining time is 1.0h, and the prepared aramid pulp.

[0036] Step 2: According to the volume ratio of aramid pulp B to water being 1.2 g: 2 L, aramid pulp B was disintegrated in water at 5000 rpm; Asphalt-based carbon fiber A was added according to the absolute dry weight ratio of asphalt-based carbon fiber A to aramid pulp B of 5:4, and then 10 mL of PEO dispersion with a concentration of 0.5 g / L was added, and then the mixture was dispersed uniformly at 25000 rpm to obtain a mixed slurry; The mixed slurry was passed through a paper sheet former to make paper, and the paper was dried after being formed to obtain asphalt-based carbon fiber paper C, wherein the drying temperature of the dryer was 120° C. and the drying time was 15 min.

[0037] Step 3: Immerse the asphalt-based carbon fiber paper C in a phenolic resin dispersion having a mass fraction of 1.0 wt% for 10 min, and then dry it at 70° C. for 30 min to obtain a dry asphalt-based carbon fiber paper D; The dried asphalt-based carbon fiber paper D was hot-pressed and finished using a flat vulcanizer at 180° C., for 8 min, and at a pressure of 10 MPa to obtain an asphalt-based carbon fiber base paper with high air permeability.

[0038] The carbon fiber base paper prepared by the high permeability asphalt-based carbon fiber base paper preparation process in this embodiment has a basis weight of 90 g / m 2 The thickness is 0.160mm, the air permeability reaches 7057 mL / min, the tensile strength is 20.31 MPa, and the square resistance is 16.52Ω / sq, which has high air permeability. In addition, the process flow is stable, the operability is strong, the comprehensive cost is controllable, and it has good social and economic benefits.

[0039] Example 3 Step 1, selecting a pitch-based carbon fiber with a length of 5 mm, a diameter of 7 μm, a resistivity of 1.7 μΩ·m, a tensile strength of 2.3 Gpa, and an elongation at break of 0.25%, soaking it in a 1% dilute hydrochloric acid solution, ultrasonically cleaning it for 6 minutes, and drying it to obtain a pitch-based carbon fiber A; The waste aramid fabric was separated and refined by a thread rolling machine, a pulping machine, a pulping machine and other equipment to obtain a specific surface area of ​​11 m 2 / g aramid pulp B; Among them, the feeding time of the thread rolling machine is 45kg / h, the beating time is 4h, and the grinding time is 0.75h.

[0040] Step 2: according to the volume ratio of aramid pulp B to water being 1.1 g: 2 L, aramid pulp B was disintegrated in water at 5700 rpm; Asphalt-based carbon fiber A was added according to the absolute dry mass ratio of asphalt-based carbon fiber A to aramid pulp B of 5.5:4, and then 7 mL of PEO dispersion with a concentration of 0.5 g / L was added, and then the mixture was dispersed uniformly at 23000 rpm to obtain a mixed slurry; The mixed slurry was passed through a paper sheet former to make paper, and the paper was dried after being formed to obtain asphalt-based carbon fiber paper C, wherein the drying temperature of the dryer was 115° C. and the drying time was 13 min.

[0041] Step 3: Immerse the asphalt-based carbon fiber paper C in a phenolic resin dispersion having a mass fraction of 0.9 wt% for 7 minutes, and then dry it at a temperature of 65° C. for 25 minutes to obtain a dry asphalt-based carbon fiber paper D; The dried asphalt-based carbon fiber paper D was hot-pressed and finished using a flat vulcanizer at 165° C., for 7 min, and at a pressure of 8 MPa to obtain an asphalt-based carbon fiber base paper with high air permeability.

[0042] The carbon fiber base paper prepared by the high permeability asphalt-based carbon fiber base paper preparation process in this embodiment has a basis weight of 70 g / m 2 , thickness is 0.142mm, air permeability reaches 7548 mL / min, tensile strength is 23.43 MPa, square resistance is 15.34Ω / sq, with high air permeability, reference Figure 2 , the carbon fiber and aramid pulp on its surface form an interwoven network with gas channels in the middle, which further indicates the reason for its high air permeability.

[0043] Example 4 Step 1, selecting a pitch-based carbon fiber with a length of 5 mm, a diameter of 7 μm, a resistivity of 1.5 μΩ·m, a tensile strength of 2.2 Gpa, and an elongation at break of 0.25%, soaking it in a 2% dilute hydrochloric acid solution, ultrasonically cleaning it for 5 minutes, and drying it to obtain a pitch-based carbon fiber A; The waste aramid fabric was separated and refined by a thread rolling machine, a pulping machine, a pulping machine and other equipment to obtain a specific surface area of ​​11 m 2 / g of aramid pulp B; wherein, the feeding time of the thread rolling machine is 42kg / h, the beating time is 3.5h, and the grinding time is 0.8h, to prepare the aramid pulp.

[0044] Step 2: According to the volume ratio of aramid pulp B to water of 1.0 g: 2 L, aramid pulp B was dispersed in water at 5500 rpm; asphalt-based carbon fiber A was added according to the absolute dry mass ratio of asphalt-based carbon fiber A to aramid pulp B of 5.5:4, and then 8 mL of PEO dispersion with a concentration of 0.5 g / L was added, and then dispersing at 23000 rpm to uniformly disperse to obtain a mixed slurry; The mixed slurry was passed through a paper sheet former to make paper, and the paper was dried after being formed to obtain asphalt-based carbon fiber paper C, wherein the drying temperature of the dryer was 115° C. and the drying time was 14 minutes.

[0045] Step 3: Immerse the asphalt-based carbon fiber paper C in a phenolic resin dispersion having a mass fraction of 0.9 wt% for 8 minutes, and then dry it at a temperature of 65° C. for 25 minutes to obtain a dry asphalt-based carbon fiber paper D; The dried asphalt-based carbon fiber paper D was hot-pressed and finished using a flat vulcanizer at 165° C., for 6 min, and under a pressure of 7 MPa to obtain an asphalt-based carbon fiber base paper with high air permeability.

[0046] The carbon fiber base paper prepared by the high permeability asphalt-based carbon fiber base paper preparation process in this embodiment has a basis weight of 80 g / m 2 , thickness is 0.149mm, air permeability reaches 7821 mL / min, tensile strength is 25.21 MPa, square resistance is 17.53Ω / sq, with high air permeability, reference Figure 3 The carbon fiber and aramid pulp are interwoven on its surface, and there are abundant pores.

[0047] Example 5 Step 1, selecting a pitch-based carbon fiber with a length of 7 mm, a diameter of 8 μm, a resistivity of 1.9 μΩ·m, a tensile strength of 2.3 Gpa, and an elongation at break of 0.25%, soaking it in a 1% dilute hydrochloric acid solution, ultrasonically cleaning it for 10 minutes, and drying it to obtain a pitch-based carbon fiber A; The waste aramid fabric was separated and refined by a thread rolling machine, a pulping machine, a pulping machine and other equipment to obtain a specific surface area of ​​11 m 2 / g of aramid pulp B; wherein, the feeding time of the thread rolling machine is 45kg / h, the beating time is 3.5h, and the grinding time is 0.9h.

[0048] Step 2: disintegrate the aramid pulp B in water at 5700 rpm according to the volume ratio of the aramid pulp B to water of 1.1 g: 2 L; Then, the asphalt-based carbon fiber A was added according to the absolute dry mass ratio of asphalt-based carbon fiber A to aramid pulp B of 5.4:4, and then 6 mL of PEO dispersion with a concentration of 0.5 g / L was added, and then the mixture was dispersed uniformly at 22000 rpm to obtain a mixed slurry; The mixed slurry was passed through a paper sheet former to make paper, and the paper was dried after being formed to obtain asphalt-based carbon fiber paper C, wherein the drying temperature of the dryer was 117° C. and the drying time was 13 min.

[0049] Step 5: Immerse the asphalt-based carbon fiber paper C in a phenolic resin dispersion having a mass fraction of 0.85 wt% for 8 minutes, and then dry it at a temperature of 67° C. for 27 minutes to obtain a dry asphalt-based carbon fiber paper D; Finally, the dried asphalt-based carbon fiber paper D was hot-pressed and finished using a flat vulcanizer at 165° C., for 6 min, and at a pressure of 8 MPa to obtain an asphalt-based carbon fiber base paper with high air permeability.

[0050] The carbon fiber base paper prepared by the high permeability asphalt-based carbon fiber base paper preparation process in this embodiment has a basis weight of 80 g / m 2 The thickness is 0.147mm, the air permeability reaches 7953 mL / min, the tensile strength is 26.64 MPa, and the square resistance is 16.89Ω / sq, which has high air permeability. In addition, the process flow is stable, the operability is strong, the comprehensive cost is controllable, and it has good social and economic benefits.

[0051] Table 1 Technical parameters of carbon fiber base paper prepared in Examples 1 to 5

[0052] Table 1 shows the technical parameters of the carbon fiber base paper prepared in the embodiment. From the data analysis, it can be obtained that the carbon fiber base paper prepared by the process route provided by the present invention has an air permeability of 7548-8104 mL / min, which is a relatively high level. This is because the asphalt-based carbon fiber and aramid pulp are fully interwoven, but the high porosity is retained; the tensile strength of the carbon fiber base paper in the embodiment exceeds 20 MPa, reaching a relatively high strength. This is because on the one hand, the aramid pulp has hydrogen bonding and strong interweaving force, and on the other hand, the contact point between the carbon fiber and the aramid pulp is strengthened by impregnation and curing of the phenolic resin.

[0053] The above description is only a preferred embodiment of the present invention and is not intended to impose any limitation on the technical solution of the present invention. Those skilled in the art should understand that, without departing from the spirit and principles of the present invention, the technical solution can also be subjected to several simple modifications and substitutions, and these modifications and substitutions are also within the scope of protection covered by the claims.

Claims

1. A process for preparing high-permeability asphalt-based carbon fiber base paper, characterized in that: The steps include: Step 1, soaking the asphalt-based carbon fiber in a dilute hydrochloric acid solution, and then ultrasonically cleaning and drying to obtain the asphalt-based carbon fiber A; The waste aramid fabric is subjected to filament separation and brooming by rubbing, beating and refining to obtain aramid pulp B with high specific surface area, high terminal bifurcation and high interweaving force; Step 2: First, the aramid pulp B is deflated in water, and then the asphalt-based carbon fiber A and PEO dispersion are added to deflate again, and then the asphalt-based carbon fiber paper C is obtained by forming and drying; Step 3: The asphalt-based carbon fiber paper C is immersed in a phenolic resin dispersion solution, and then dried and hot-pressed to obtain an asphalt-based carbon fiber base paper with high air permeability.

2. The process for preparing a high-permeability asphalt-based carbon fiber base paper according to claim 1, characterized in that: In step 1, the relevant requirements of the asphalt-based carbon fiber are as follows: length is 3-8 mm, diameter is 7-8 μm, resistivity is 1.5-2.0 μΩ·m, tensile strength is 2.2-2.4 Gpa, and elongation at break is 0.25%-0.26%; The concentration of dilute hydrochloric acid is 1-2%, the ultrasonic treatment time is 5-10 minutes, the drying temperature is 100-105°C, and the time is 15-25 minutes.

3. The process for preparing a high-permeability asphalt-based carbon fiber base paper according to claim 1, characterized in that: In step 1, the waste aramid fabric is para-aramid fiber, which is mainly sourced from discarded bulletproof vests and scraps from woven fabric production.

4. The process for preparing a high-permeability asphalt-based carbon fiber base paper according to claim 1, characterized in that: In step 1, the feeding time of the thread rolling machine is 40-50 kg / h, the beating time of the beater is 3-5 h, the refining time of the refiner is 0.5-1.0 h, and the specific surface area of ​​aramid pulp B is 10-12 m 2 / g.

5. The process for preparing a high-permeability asphalt-based carbon fiber base paper according to claim 1, characterized in that: In step 2, the ratio of aramid pulp B to water is 1.0-1.2 g: 2 L, and the disintegration speed is 5000-6000 rpm.

6. The process for preparing a high-permeability asphalt-based carbon fiber base paper according to claim 1, characterized in that: In step 2, the absolute dry mass ratio of the asphalt-based carbon fiber A to the aramid pulp B is 6-5:4, the concentration of the PEO dispersion is 0.5 g / L, the volume is 5-10 mL, and the disintegration speed is 20000-25000 rpm.

7. The process for preparing high-permeability asphalt-based carbon fiber base paper according to claim 1, characterized in that: In step 2, during drying, the temperature is 110-120° C. and the time is 10-15 minutes.

8. The process for preparing high-permeability asphalt-based carbon fiber base paper according to claim 1, characterized in that: In step 3, the phenolic resin dispersion solution is industrial grade ethanol, the mass fraction is 0.8 wt% to 1.0 wt%, and the immersion time is 5 to 10 min.

9. The process for preparing high-permeability asphalt-based carbon fiber base paper according to claim 1, characterized in that: In step 3, during drying, the temperature is 60-70° C. and the time is 20-30 min; during hot pressing finishing, the temperature is 150-180° C., the time is 5-8 min, and the pressure is 6-10 MPa.

10. A pitch-based carbon fiber base paper obtained by the process for preparing a high-permeability pitch-based carbon fiber base paper according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Carbon fiber paper construction & manufacturing process

    US20060214320A1

  • Porous carbon electrode substrate, method of manufacturing same, gas diffusion layer, and membrane-electrode assembly for fuel cell

    US20180069245A1

  • Carbon fiber paper for solid polymer fuel cells

    US6489051B1

  • Method for producing aramid fiber pulp by aramid fiber waste material

    CN101250771A

  • Preparation method of carbon fiber paper

    CN113584940A

Cited By

  • Nanometer friction paper-based positive electrode material with interpenetrating network structure and preparation method of nanometer friction paper-based positive electrode material

    CN119800772A

  • Carbon paper for fuel cell and preparation method thereof

    CN119800773A

  • Resin cross-linked shaped carbon fiber conductive base paper for hydrogen fuel cell and preparation process of resin cross-linked shaped carbon fiber conductive base paper

    CN119900195A

  • Resin crosslinking and setting carbon fiber conductive base paper for hydrogen fuel cell and preparation process thereof

    CN119900195B